2022
DOI: 10.3390/cells11182918
|View full text |Cite
|
Sign up to set email alerts
|

Purkinje Cell Patterning—Insights from Single-Cell Sequencing

Abstract: Despite their homogeneous appearance, Purkinje cells are remarkably diverse with respect to their molecular phenotypes, physiological properties, afferent and efferent connectivity, as well as their vulnerability to insults. Heterogeneity in Purkinje cells arises early in development, with molecularly distinct embryonic cell clusters present soon after Purkinje cell specification. Traditional methods have characterized cerebellar development and cell types, including Purkinje cell subtypes, based on knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 79 publications
(157 reference statements)
1
7
0
Order By: Relevance
“…In addition to the migration of granule cells during cerebellar development, the migration of Purkinje cell precursors outward from the ventricular zone and their alignment into a monolayer are required to form the three-layered cortical structure. 15 In the present study, we observed misaligned Purkinje cells that were exclusively immunoreactive with CALB1 in the GBH group at weaning, whereas the number of the Purkinje cells at this time was unchanged in the GBH group. Several in vivo studies using transgenic mice found that delayed migration of granule cells to the IGL disrupts the alignment of their synaptic partners, namely Purkinje cells.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…In addition to the migration of granule cells during cerebellar development, the migration of Purkinje cell precursors outward from the ventricular zone and their alignment into a monolayer are required to form the three-layered cortical structure. 15 In the present study, we observed misaligned Purkinje cells that were exclusively immunoreactive with CALB1 in the GBH group at weaning, whereas the number of the Purkinje cells at this time was unchanged in the GBH group. Several in vivo studies using transgenic mice found that delayed migration of granule cells to the IGL disrupts the alignment of their synaptic partners, namely Purkinje cells.…”
Section: Discussionsupporting
confidence: 45%
“…Granule cells in the IGL outgrow axons and continue to grow the ML until the beginning of week seven after birth 13,14 . Purkinje cells are generated in the ventricular zone, where they proliferate and then migrate outward, eventually forming a single‐cell layer in the early postnatal period 15 . The cerebellum has a diverse distribution of interneurons, including basket/stellate cells in the ML and unipolar brush cells, Golgi cells, and Lugaro cells in the IGL/GL, which form a sophisticated neural network along with granule cells and Purkinje cells 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on single-cell studies, at least 4 “embryonic” clusters of PCs can be identified in the developing cerebellum with a specified set of marker genes unique to this developmental window 62 . Although SCA7 mice retain parasagittal striping of the cerebellum at 5 weeks of age, evidence for gene expression alterations in zebrin identity genes are already present at this time point ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on single-cell studies, at least 4 "embryonic" clusters of PCs can be identified in the developing cerebellum with a specified set of marker genes unique to this developmental window 62 .…”
Section: Discussionmentioning
confidence: 99%